Exploration of the Anxiolytic Potential of Red Shoot Leaf Extract through Elevated Plus Maze and Light-Dark Box Tests in White Mice - Sari Nurdian; Triyana Agustin; Novita Yelica Umina; Helman Kurniadi (Biology, Medicine, & Natural Product Chemistry, 2026)
Anxiety disorders remain a major global mental health concern, with increasing prevalence and limitations associated with long-term pharmacotherapy. This study aimed to evaluate the anxiolytic potential of ethanol extract of Syzygium myrtifolium leaves using in vivo behavioral models. Dried leaves were extracted by maceration with 96% ethanol, yielding 16.69% extract. The results of phytochemical screening demonstrated the presence of flavonoids, alkaloids, tannins, saponins, as well as terpenoids. Fifteen male white mice were randomly divided into five groups: negative control (0.5% Na-CMC), positive control (diazepam 1 mg/kgBW), and extract-treated groups (100, 200, and 300 mg/kgBW). Anxiolytic activity was assessed using the Elevated Plus Maze (EPM) and Light–Dark Box (LDB) tests. In the EPM model, extract doses of 200 and 300 mg/kgBW significantly increased the time spent in open arms compared to the negative control (p < 0.05). Similarly, in the LDB test, higher extract doses significantly prolonged the duration in the illuminated compartment (p < 0.05). Statistical analysis confirmed normal data distribution and significant differences among groups (ANOVA, p < 0.05). The findings indicate that Syzygium myrtifolium leaf extract exhibits significant anxiolytic-like activity, likely associated with its flavonoid content and antioxidant properties. These results support its potential development as a plant-based alternative therapy for anxiety management.